THE EFFECT OF THE FAMILY ENVIRONMENT ON STUDENTS' LEARNING ACHIEVEMENTS IN SOCIAL SCIENCE SUBJECT THROUGH LEARNING MOTIVATION AT SMP TEKNOLOGI PEKANBARU - Irfandi Hernaldi; Rr. Sri Kartikowati; Gimin Gimin (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
Education is a barometer of a nation's progress; thus, it is not surprising that education becomes one of the important issues to be seriously improved. The low learning achievement of grade VII students at SMP Teknologi Pekanbaru, especially in social science subjects that was influenced by the family environment, was the background of this research problem. This research applied descriptive quantitative research methods and the purpose of this research was to determine the influence of the family environment on students' learning achievements in social science subject through learning motivation at SMP Teknologi Pekanbaru. Data were collected through documentation to obtain students’ learning achievements and questionnaires to obtain data about the family environment and learning motivation. The population in this research was 68 grade VII students and the samples were selected through census sampling techniques meaning that the entire population was selected samples. After that, the data were tabulated and analyzed by using path analysis assisting by SPSS version 25. The results showed that the family environment indirectly had a positive and significant impact on the students’ learning achievements in social science subject through learning motivation at SMP Teknologi Pekanbaru.